THE T21 PROJECT: A EUROPEAN INITIATIVE FOR YOUNG PEOPLE WITH SPECIAL EDUCATIONAL NEEDS - Matos, Pedro (2020)
Awareness raising for the inclusion of the citizen with Trisomy 21 has been increasing slowly thanks to a series of measures and actions taken at national and European level. The European Parliament adopted a declaration on children with Down syndrome in 2012, encouraging the Commission, the Council and the Member States to contribute to their social inclusion through awareness-raising campaigns. The EU also promotes its inclusion in society through the European disability strategy, but much more can and must be done. The work in this area is still mainly carried out by non-profit organizations and social entities with very few resources. Thus, the project T21 aims to make a positive difference in the area of support for children such as Down syndrome.